Field Performance of ‘Valencia’ Sweet Orange Trees Grafted onto Pummelo Interstocks and Swingle Citrumelo Rootstocks under Huanglongbing (HLB) Endemic Conditions - Manjul Dutt; Lamiaa M. Mahmoud; Jude W. Grosser (Horticulturae, 2023)
Interstocks have been used in fruit tree cultivation to regulate tree size and improve fruit production and quality. In this study, several Huanglongbing (HLB)-tolerant open-pollinated pummelo interstock candidates were evaluated as interstocks between the Swingle rootstock and the ‘Valencia’ scion, with Swingle serving as the control interstock. After 5 years in the field, most trees did not exhibit visual HLB symptoms, although the trees were infected with HLB, and the CaLas Ct values in the ‘Valencia’ leaves of the different interstock treatments ranged between 25.88 and 27.82. Although the foliar chlorophyll content among the interstock treatments was not highly significant (p-value = 0.0313), the foliar starch content was significantly different (p-value = 0.0018). ‘Valencia’ grafted onto 5-1-99-3 and HBJL-4 interstocks (both open pollinated seedlings of the Hirado Buntan pummelo) exhibited the highest total phenolic compound (TPC) levels (46.44 and 46.36 mg gallic acid g−1 FW). Transcripts of CsPR1 and CsPR2, two pathogenesis-related (PR) genes, were upregulated in ‘Valencia’ grafted onto open pollinated seedling selections of the red shaddock pummelo, Liang Ping Yau pummelo, and Hirado Buntan pummelo compared with ‘Valencia’ grafted onto Swingle. All interstocks influenced the tree growth rate and improved canopy volume in the field compared to the control trees without any interstocks (p-value = 0.0085). The 5-4-99-7 (red shaddock pummelo) and 8-1-99-1B (Liang Ping Yau pummelo) interstock trees had the highest canopy volume among all the treatments. We propose, based on our current results, that HLB-tolerant citrus accessions, when judiciously used as interstocks, may enhance plant defense and provide increased HLB tolerance to susceptible scions.